(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. Currently, platinum compounds are the only metal-containing drugs used for the treatment of various types of malignant tumors. Since, cisplatin and its analogues are toxic drugs, healthy tissues and organs suffer greatly from their action. Therefore, considerable attention of researchers is devoted to the study of less toxic analogues of cisplatin, in particular other metals of the platinum group, and compounds with mechanisms of cytotoxic action that differ from cisplatin. Intercalation is one of such mechanisms. Intercalators are compounds with a planar structure, or those that at least include a fragment of corresponding structure. These can be palladium compounds with planar ligands, in particular with derivatives of 3-(2-pyridyl)-1,2,4-triazoles. Methods. The interaction of the ligand and palladium complexes with DNA and ovalbumin was studied by fluorescence spectroscopy. Results. A sharp increasing of the excitation and fluorescence spectra intensities of the DNA solution at the presence of a coordinatively saturated palladium complex based on PdL2 was established. At the same time, the appearance of an isosbestic point on the excitation spectra confirms the interaction between DNA and PdL2 and shows the possibility of small planar molecules of such complex to intercalate into the DNA double helix. A significant decrease in the fluorescence intensity of the DNA solution at the presence of coordinatively unsaturated complex Pd(HL)Cl2 was observed. Individual ligand has almost no effect on the fluorescence of DNA, but it leads to an increase in the fluorescence of the ovalbumin solution, which indicates the possibility of using 2-(3-methyl)-5-pyridyl-1,2,4-triazole as a fluorescent reagent for albumin. The fluorescence intensity of ovalbumin decreases after adding of Pd(HL)Cl2 and PdL2 complexes. The obtained results confirm the possibility of the coordinatively saturated palladium complex based on 2-(3-methyl)-5-pyridyl-1,2,4 triazole to interact with DNA by the intercalation mechanism and indicate the relevance of further development of fluorescent systems based on 2-(3-methyl)-5-pyridyl-1,2,4 triazole for the detection of albumins. Conclusions. Interaction of coordinatively saturated palladium complex PdL2 based on 2-(3-methyl)-5-pyridyl-1,2,4-triazole with DNA by the intercalation mechanism was established. Unlike DNA, interaction of both Pd(HL)Cl2 and PdL2 complexes with ovalbumin solution results in protein denaturation. However, when HL is added to the ovalbumin solution, the fluorescence intensity of the protein increases.